The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1111/den.13404
|View full text |Cite
|
Sign up to set email alerts
|

Modified laser‐based photodynamic endoscopic diagnosis for early gastric cancer

Abstract: https://onlinelibrary.wiley.com/page/journal/14431661/den13404-sup-0001-vids1.htm a video of this article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Example case of PDD endoscopy of gastric tumor with Si2-P2 ® system is reported in the literature (15). Example cases of PDD using Si2 P2 ® system are presented in Figure 1.…”
Section: New Endoscopic System For Pddmentioning
confidence: 99%
“…Example case of PDD endoscopy of gastric tumor with Si2-P2 ® system is reported in the literature (15). Example cases of PDD using Si2 P2 ® system are presented in Figure 1.…”
Section: New Endoscopic System For Pddmentioning
confidence: 99%
“…However, the first endoscopic identification of gastric tumors is usually performed by white-light endoscopy, because magnification is needed for full utilization of the NBI method in the identification of gastric tumors. Photodynamic diagnosis (PDD) endoscopy after oral intake of 5-aminolevulinic acid (5-ALA) has proven useful for detecting gastric tumors [ 4 , 5 , 6 ]. A recent study found additional lesions that were identified as tumors in 13 cases with the use of PDD endoscopy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We reported diagnostic yield of laser-based photodynamic diagnosis (PDD) for gastric neoplasms, but the dark images and weak fluorescence contrast remained unsatisfactory. [2][3][4] PDD is based on 5-aminolevulinic acid (5-ALA) being metabolized into protoporphyrin IX, which accumulates in tumor cells; when exciting around 410-nm light, tumor cells emit red fluorescence at 635 nm. We have trialed a new prototype light-emitting diode (LED)-based PDD system that can provide monochromatic excitation light.…”
mentioning
confidence: 99%